Some Integral Inequalities for Quasimonotone Functions in Weighted Variable Exponent Lebesgue Space with 0 < p(x) < 1 - Senouci, Abdelkader; Zanou, Abdelkader (Eurasian Mathematical Journal, 2020)
The aim of this paper is to obtain some weighted Hardy’s inequalities for quasi-monotone functions in weighted variable exponent Lebesgue space with 0 < p(x) < 1.